The Relation of The Family Resilience with Substance on Skizofrenia Patients in The Psikiatri Unit - Nurmaela Mela Nurmaela; Suryani Suryani; Imas Rafiyah (JKP (Jurnal Keperawatan Padjajaran), 2018)
Abstract